Fibrodysplasia Ossificans Progressiva: A Case Report - Acharya, Sudeep; Joshi, Sandhya; Chaulagain, Rajib (Journal of Nepal Health Research Council, 2018)
Fibrodysplasia ossificans progressiva is a genetic disorder of the connective tissue differentiation characterized by congenital malformation of the big toes and progressive heterotopic ossification in the extra skeletal tissues like tendons, ligaments, fascia and skeletal muscles leading to permanent disability. The prevalence is one in two million people. During childhood, it may be asymptomatic but in later life, progressive stiffness of major joints renders movement of the individual impossible. Currently, there is no effective treatment for this debilitating disease. Here, we present a case of 27 year old male with clinical and radiological features of fibrodysplasia ossificans progressiva. Keywords: Fibrodysplasia ossificans progressive; heterotopic ossification; myositis ossificans; myositis ossificans progressive.